EVALUATION OF STUDYING BEHAVIORS OF SECONDARY SCHOOL STUDENTS IN SCIENCE AND ARTS CENTERS: KARTAL PROF. DR. SABAN DURALI SCIENCE AND ART CENTER EXAMPLE - YÜKSEL, Hüseyin Kadir; GÖNEN , İlker; KILIÇ , Oktay; TÜYSÜZ, Harun; YILDIZ , Güven (SSD Journal, 2021)
The aim of the research is; "It is the evaluation of the studying behavior of secondary school students enrolled in science and arts centers. The universe of the research was created by secondary school students enrolled at Istanbul Kartal Prof.Dr. Şaban Teoman Duralı Science and Arts Center. In the research, "Personal Information Form" and Baltaş's “Studying Behavior Evaluation Scale” were used as a data collection tool. The data obtained were evaluated separately for each type of program in which students were enrolled in the sub-dimensions of starting and continuing to study, working consciously and using what they learned, taking notes and listening to the lesson, reading habits, preparing homework, attitude towards school, preparing for exams and taking the exam. As a result of the evaluation, maps of the studying behavior of secondary school students diagnosed as special talents were made and recommendations were presented for the guidance work to be done to strengthen their weaknesses